PROSPEK PERDAGANGAN LUAR NEGERI INDONESIA – AMERIKA SERIKAT DAN KURS - Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT This study aims to identify and analyze: (a) the effect of the ratio of the money supply, real output ratio, the difference in inflation, interest rate differentials and foreign trade Indonesia-USA on the exchange rate IDR/US , (b) the influence of the ratio of real output Indonesi -the United States, the ratio of real output and the Indonesia-Japan exchange rate IDR/U.S. against Indonesia's foreign trade-the United States, and (c) foreign trade prospects for Indonesia and the United States. The data used in the study is the time series of the year 1997:3 until 2009:4. The data are stationary at different degrees, but both models cointegration analysis. Furthermore, both models are tested in the identification, reduced form and causality endogenous variables, the two models are estimated using the method of simultaneous equations with 2SLS (Two Stage Least Squares. The results of this study show that: (a) the ratio of the money supply, real output ratio, the difference in inflation, interest rate differentials and foreign trade of the United States Indonesia-significant effect on the exchangeÂ rate of IDR/U.S. , (b) the real output ratio of Indonesia-USA, the ratio of real output the Indonesia-Japan and exchange rate IDR/U.S. significant effect on Indonesia's foreign trade-the United States, and (c) foreign trade Indonesia and the United States have a positive outlook until 2017. From this research, the study recommends to the government of Indonesia through the Ministry of Industry and Trade to continue to give encouragement to the foreign trade sector to increase the quantity and the qualityÂ and diversification of exported commodities that Indonesia's foreign trade prospects-the United States can be realized. Keyword: foreign trade, exchange rates, real output and money supply.